The synergic effects of presynaptic calcium channel antagonists purified from spiders on memory elimination of glutamate-induced excitotoxicity in the rat hippocampus trisynaptic circuit - Keimasi, Mohammad; Salehifard, Kowsar; Mirshah Jafar Esfahani, Noushin; Esmaeili, Fariba; Farghadani, Arman; Amirsadri, Mohammadreza; Keimasi, Mohammadjavad; Noorbakhshnia, Maryam; Moradmand, Majid; Mofid, Mohammad Reza (Frontiers in Molecular Biosciences, 2023)
Hippocampus is a complex area of the mammalian brain, which is responsible for learning and memory. The trisynaptic circuit engages with explicit memory. Hippocampal neurons express two types of presynaptic voltage-gated calcium channels (VGCCs) comprising N and P/Q-types. These VGCCs have a vital role in the release of neurotransmitters from presynaptic neurons. The chief excitatory neurotransmitter at these synapses is glutamate. Glutamate has an essential function in learning and memory under normal conditions. The release of neurotransmitters depends on the activity of presynaptic VGCCs. Excessive glutamate activity, due to either excessive release or insufficient uptake from the synapse, leads to a condition called excitotoxicity. This pathological state is common among all neurodegenerative disorders, such as Alzheimer's, and Parkinson's diseases. Under these conditions, glutamate adversely affects the trisynaptic circuitry, leading to synaptic destruction and loss of memory and learning performance. This study attempts to clarify the role of presynaptic VGCCs in memory performance and reveals that modulating presynaptic calcium channels activity in the trisynaptic pathway can regulate excitotoxic state and consequently, prevents elimination of neurons, and synaptic degradation. All these can lead to improvement in learning and memory function. In the current study, two calcium channel blockers, including omega-agatoxin-Aa2a and omega-Lsp-IA, were extracted, purified, and identified from (Agelena orientalis, and Hogna radiata) spiders, and were used to modulate N and P/Q-VGCCs. The effect of the omega-agatoxin-Aa2a, and omega-Lsp-IA on the glutamate-induced excitotoxicity in rats was evaluated via the Morris Water Maze task as a behavioral test. The local expression of synaptophysin (SYN) was visualized for synaptic quantification via immunofluorescence assay. The electrophysiological amplitude of the field excitatory postsynaptic potentials (fEPSPs) in the input–output, and LTP curves of Mossy fiber and Schaffer collateral circuits was recorded. The results of our study demonstrated that N and P/Q-VGCCs modulation in the hippocampus trisynaptic circuit of rats with glutamate-induced excitotoxicity dysfunction could prevent destructive consequences of excitotoxicity in synapses and improve memory function and performance.